EXAMINATION OF EFFECTS OF ARTHYSTIC GYMNASTICS TEACHING OF PHYSICAL EDUCATION ON STATIC STRENGTH OF 3TH & 4TH GRADE PUPILS OF ELEMENTARY SCHOOLS - Dragana Aleksić; Branimir Mekić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2010)
In this work, the subject of the research is only one segment of the anthropological area, which refers to the appearance of appropriate motor abilities-coordination. Static strength Static strength is ability to retain in nonmetrics contraction of muscle that body is preserved in certain position. Static work as physical work doesn't exist in static strength, because development doesn't exist, but quality of static work the muscle should start with physiology's opinion of work. Static work is used for demonstration the power during that last.The battery for the evaluation of static strength consists of the following tests: MVIS, MIPR, MINS. During the 2005/06 academic year, a research was conducted so as to determine the effects of current program of physical education teaching on motor abilities coordination of female pupils. The research involved a total sample of 107 girls from the 3th and 4th grade of elementary school. The subjects were classified in one experimental and one control group. The experimental group was made of 59 students and they were practicing according to planning instruction where the artistic gymnastics had the primary part. The control group of 48 students was practicing according to official instructional plan and program for P.E. of the Republic of Serbia. At the beginning of the academic year, initial (first) measurement was performed, followed by experimental final (second) measurement at the end of experiment. Research data was processed using SPSS standard statistics procedure. The multi-variant procedures were used in this research ant those were: the multi-variant analysis of the variable (MANOVA) and the discriminative analysis. Also, the mono- variant procedures were used and those were: the variable analysis (ANOVA) and the interval of entrust. After the experimental treatment, i.e. at the final testing, significant differences were found with female pupils in the experimental and control groups concerning the all tests for the evaluation of static strength. The basic conclusion is that the female pupils of all,experimental groups achieved significantly higher teaching effects than the control group, in view of partly increased motor abilities, being the result of the effects of the experimental treatment, as well as other external and internal factors.